Evaluating the perceptions of the transgender and non-binary communities of pelvic radiotherapy side effect information booklets. Issue 2 (May 2020) - Burton, H.; Pilkington, P.; Bridge, P.
Abstract: Introduction: Patients undergoing radiotherapy for pelvic cancers will often experience acute and late toxicity which can result in symptoms which have a significant impact on psychosocial functioning and quality of life. Having written information regarding these symptoms enables informed decision-making and ongoing support. Transgender and non-binary communities are a marginalised but steadily growing subsection of the radiotherapy patient population yet their needs differ from those of the general population. This study aimed to evaluate the relevance of the pelvic radiotherapy patient information booklets with regard to this communities. Methods: An online survey was distributed via social media to evaluate the perceptions of these communities of four commonly distributed pelvic radiotherapy information booklets. Results: There were 19 full responses and most participants expressed discomfort regarding being provided with (11/19) or picking up (10/19) the booklets. Although most (11/19) agreed that the material in the booklets was relevant, the same number felt that the wording was not. Some of the language and assumptions made regarding the transgender and non-binary communities were incorrect and had the potential to cause distress. Conclusion: The importance of providing guidance and support to these communities was identified. Implications for practice: Further research is required to establish how best to provide inclusive patient information for transgender and non-binary individuals.